2022
DOI: 10.1007/s11033-022-07802-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute vs. chronic vs. intermittent hypoxia in breast Cancer: a review on its application in in vitro research

Abstract: Hypoxia has been linked to elevated instances of therapeutic resistance in breast cancer. The exposure of proliferating cancer cells to hypoxia has been shown to induce an aggressive phenotype conducive to invasion and metastasis. Regions of the primary tumors in the breast may be exposed to different types of hypoxia including acute, chronic or intermittent. Intermittent hypoxia (IH), also called cyclic hypoxia, is caused by exposure to cycles of hypoxia and reoxygenation (H-R cycles). Importantly, there is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…Hypoxia occurs whenever the number of cells around a blood vessel becomes too large for available O 2 delivery (Figure a). Cells might develop too quickly for the available blood supply, such as in an embryo or in a tumor, but in other cases, the blood supply may become suddenly or chronically impaired because of a wound, of PDT treatment, of ischemia, of high altitudes, or of apnea . As hypoxia is a natural phenomenon, cells have evolved different mechanisms to cope with it, which are primarily controlled by the transcription factors HIF1α and HIF2α .…”
Section: Biological and Clinical Considerations Of Ru-based Pactmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia occurs whenever the number of cells around a blood vessel becomes too large for available O 2 delivery (Figure a). Cells might develop too quickly for the available blood supply, such as in an embryo or in a tumor, but in other cases, the blood supply may become suddenly or chronically impaired because of a wound, of PDT treatment, of ischemia, of high altitudes, or of apnea . As hypoxia is a natural phenomenon, cells have evolved different mechanisms to cope with it, which are primarily controlled by the transcription factors HIF1α and HIF2α .…”
Section: Biological and Clinical Considerations Of Ru-based Pactmentioning
confidence: 99%
“…Cells might develop too quickly for the available blood supply, such as in an embryo or in a tumor, but in other cases, the blood supply may become suddenly or chronically impaired because of a wound, of PDT treatment, of ischemia, of high altitudes, or of apnea. 118 As hypoxia is a natural phenomenon, cells have evolved different mechanisms to cope with it, which are primarily controlled by the transcription factors HIF1α and HIF2α. 119 These mechanisms are highjacked in cancer cells, 120 which must always face an abnormally low state of oxygenation during early tumor development.…”
Section: Hypoxia In Oncologymentioning
confidence: 99%
“…It has been reported that hypoxic tumors are three times more resistant to therapy compared with normoxic tumors . Additionally, the limited vascularization in the hypoxic tumor acts as a barrier to the tumor permeability of the anticancer drug …”
Section: Introductionmentioning
confidence: 99%
“…31 Additionally, the limited vascularization in the hypoxic tumor acts as a barrier to the tumor permeability of the anticancer drug. 32 Therefore, considering the therapeutic requirement for treating advanced-stage breast cancers, a targeted drug delivery system may be a solution that allows the targeted delivery of the loaded drug to tumors. So, here we proposed ER targeted NPs loaded with PLB for the targeted therapy of advancedstage breast cancers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The tissue microenvironment of breast cancer is highly heterogenous and, depending on the local extent of newly formed blood vessels, it can contain regions of acute, intermittent and chronic hypoxia [10]. This is relevant as cancer cells show different cellular responses depending on the duration and frequency of hypoxia exposure [9,11,12]. Acute hypoxia is associated with reversible changes, chronic hypoxia is associated with long-term cellular changes potentially developing into mutagenesis and genetic instability [9].…”
Section: Introductionmentioning
confidence: 99%